Toggle switch residues control allosteric transitions in bacterial adhesins by participating in a concerted repacking of the protein core. - Dagmara I Kisiela; Pearl Magala; Gianluca Interlandi; Laura A Carlucci; Angelo Ramos; Veronika Tchesnokova; Benjamin Basanta; Vladimir Yarov-Yarovoy; Hovhannes Avagyan; Anahit Hovhannisyan; Wendy E Thomas; Ronald E Stenkamp; et al. (PLoS Pathogens, 2021)
Critical molecular events that control conformational transitions in most allosteric proteins are ill-defined. The mannose-specific FimH protein of Escherichia coli is a prototypic bacterial adhesin that switches from an 'inactive' low-affinity state (LAS) to an 'active' high-affinity state (HAS) conformation allosterically upon mannose binding and mediates shear-dependent catch bond adhesion. Here we identify a novel type of antibody that acts as a kinetic trap and prevents the transition between conformations in both directions. Disruption of the allosteric transitions significantly slows FimH's ability to associate with mannose and blocks bacterial adhesion under dynamic conditions. FimH residues critical for antibody binding form a compact epitope that is located away from the mannose-binding pocket and is structurally conserved in both states. A larger antibody-FimH contact area is identified by NMR and contains residues Leu-34 and Val-35 that move between core-buried and surface-exposed orientations in opposing directions during the transition. Replacement of Leu-34 with a charged glutamic acid stabilizes FimH in the LAS conformation and replacement of Val-35 with glutamic acid traps FimH in the HAS conformation. The antibody is unable to trap the conformations if Leu-34 and Val-35 are replaced with a less bulky alanine. We propose that these residues act as molecular toggle switches and that the bound antibody imposes a steric block to their reorientation in either direction, thereby restricting concerted repacking of side chains that must occur to enable the conformational transition. Residues homologous to the FimH toggle switches are highly conserved across a diverse family of fimbrial adhesins. Replacement of predicted switch residues reveals that another E. coli adhesin, galactose-specific FmlH, is allosteric and can shift from an inactive to an active state. Our study shows that allosteric transitions in bacterial adhesins depend on toggle switch residues and that an antibody that blocks the switch effectively disables adhesive protein function.